2018
DOI: 10.1111/acps.12973
|View full text |Cite
|
Sign up to set email alerts
|

ICD‐11 PTSD and complex PTSD amongst Syrian refugees in Lebanon: the factor structure and the clinical utility of the International Trauma Questionnaire

Abstract: Objective Support for ICD‐11 post‐traumatic stress disorder (PTSD) and complex PTSD (CPTSD) is growing; however, few studies include refugees or examine the clinical utility of PTSD/CPTSD classifications. This study sought to provide the first evaluations of (i) the factor structure of ICD‐11 PTSD/CPTSD amongst refugees in the Middle East; and (ii) the clinical utility of the International Trauma Questionnaire (ITQ) to identify PTSD/CPTSD in a humanitarian context. Method Participants were 112 treatment‐seekin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
102
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 30 publications
(50 reference statements)
14
102
1
2
Order By: Relevance
“…First, the low rates of PTSD and CPTSD found in the non-clinical sample of young adults precluded generating more unique differentiations between PTSD and DSO symptom clusters. This is consistent with previous research showing that the second-order model fitted better than the first-order model in clinical (Cloitre et al, 2018) and highly traumatised samples, such as refugees (Vallières et al, 2018), and the first-order model fitted better in population studies (Ben-Ezra et al, 2018;Shevlin et al, 2017). Second, it is possible that symptoms of PTSD and CPTSD are less clearly delineated in the Chinese population.…”
Section: Discussionsupporting
confidence: 90%
“…First, the low rates of PTSD and CPTSD found in the non-clinical sample of young adults precluded generating more unique differentiations between PTSD and DSO symptom clusters. This is consistent with previous research showing that the second-order model fitted better than the first-order model in clinical (Cloitre et al, 2018) and highly traumatised samples, such as refugees (Vallières et al, 2018), and the first-order model fitted better in population studies (Ben-Ezra et al, 2018;Shevlin et al, 2017). Second, it is possible that symptoms of PTSD and CPTSD are less clearly delineated in the Chinese population.…”
Section: Discussionsupporting
confidence: 90%
“…A moderate-to-strong correlation between the PTSD and DSO factors indicated that the constructs are conceptually overlapping but not interchangeable as only 45% of the variance was shared between the two factors. The results are very similar to those examining the latent structure of the ITQ Karatzias et al, 2016;Kazlauskas et al, 2018;Vallières et al, 2018). It is encouraging that the latent structure of the ICD-11 symptoms of PTSD and CPTSD is consistent across self-reported and clinicianadministered measures.…”
Section: Discussionsupporting
confidence: 70%
“…Studies using preliminary versions of the ITQ with samples exposed to various types of traumas and from diverse cultural backgrounds suggest that the instrument is a valid and reliable tool. Factor analyses indicate good fit for the ICD-11 model of CPTSD (i.e., a secondorder hierarchical model separating PTSD and DSO symptomatology), although there is also support for a model that distinguishes between these symptoms at the first-order level (Ben-Ezra et al, 2018;Hyland et al, 2017;Karatzias et al, 2016;Kazlauskas, Gegieckaite, Hyland, Zelviene, & Cloitre, 2018;Nickerson et al, 2016;Vallières et al, 2018). In general, PTSD symptoms have been found to be associated with measures of fear and anxiety whereas DSO symptoms show stronger associations with measures of depression, dysthymia, and general distress.…”
Section: Introductionmentioning
confidence: 89%
“…Considerable evidence is accumulating to support the proposed factorial validity of ICD-11 CPTSD (Hyland et al, 2017a;Karatzias et al, 2016) including two studies of refugees (Nickerson et al, 2016;Vallières et al, 2018). On the other hand, investigations evaluating the factor structure of PTSD and CPTSD in a sample of West Papuan refugees displaced to Papua New Guinea questioned the appropriateness of the CPTSD construct for trauma-exposed refugees (Tay, Rees, Chen, Kareth, & Silove, 2015) and suggested that refugee populations exposed to persecution and the traumas of human rights violations are distinctive in showing a general traumatic stress response in which ICD-11 specified PTSD and CPTSD features are indissolubly represented (Silove, Tay, Kareth, & Rees, 2017).…”
Section: Introductionmentioning
confidence: 99%